2002
DOI: 10.1017/s0956536102132184
|View full text |Cite
|
Sign up to set email alerts
|

Bajo Sediments and the Hydraulic System of Calakmul, Campeche, Mexico

Abstract: Maya Lowlands climate researchers have set aside earlier beliefs that Maya civilization flourished in an unchanging environment. Analyses of river discharge, weather patterns, lake-bottom sediments, and settlement patterns reveal a highly variable climate, considerable diversity in local geology and soils, and a wide range of cultural adaptations tailored to distinctive subregional settings. Significant knowledge gaps remain. Among the unanswered questions is how cities in the elevated interior were maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 18 publications
(20 reference statements)
0
49
0
2
Order By: Relevance
“…Some of the evidence is direct, such as the evidence for settlements and monumental architecture, terraces, and wetland fields. Other evidence is indirect, including orchard gardens, managed forests, and possible cultivation along modified edges of seasonal wetlands (66). The evidence for orchard gardens is based on the archaeological record of vegetative remains in middens, suggesting a long history of a strong reliance on fruits and nuts (84)(85)(86)(87), and walled spaces around house sites, indicating orchard gardens as described by the Spaniards (83, 88).…”
Section: Human-environment Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the evidence is direct, such as the evidence for settlements and monumental architecture, terraces, and wetland fields. Other evidence is indirect, including orchard gardens, managed forests, and possible cultivation along modified edges of seasonal wetlands (66). The evidence for orchard gardens is based on the archaeological record of vegetative remains in middens, suggesting a long history of a strong reliance on fruits and nuts (84)(85)(86)(87), and walled spaces around house sites, indicating orchard gardens as described by the Spaniards (83, 88).…”
Section: Human-environment Interactionsmentioning
confidence: 99%
“…Despite managed forests, wood fuel and construction timber became increasingly scarce as did, perhaps, large mammals (meat sources). To maintain a sufficient water supply, small aquadas (ponds) and major reservoirs were constructed, and the edges of seasonal wetlands were manipulated to hold water (65,66,69,71).…”
Section: Environmental Stress Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars began to suspect the role of drought in Maya history by associating Mesoamerican with European trends (21,22), but the first regional evidence came in the 1990s based on retrodicting the discharge of the Rio Candelaria, Mexico, with models of global insolation, atmospheric patterns, and volcanic emissions that indicated higher rainfall in the Classic Period and dryer conditions in the Terminal Classic (23,24). Lake core studies at Chichancanab and Punta Laguna, also in the 1990s, indicated climate change in the Yucatán based on the relative abundance of sulfur (S) to calcite (CaCO 3 ) in sediments and oxygen isotope ratios (δ 18 O) in benthic shells (25)(26)(27)(28).…”
Section: Climate and Evidence For Droughtmentioning
confidence: 99%
“…Thanks to inexpensive transportation costs, they were not using their forest cover, but rather building on it through the use of arboriculture during their long ascent to power. This efficient use of coastal area forests has been observed ethnographically on both the east and west coasts (Gunn et al 2002, Ford and Nigh 2009, 2015. So, the covariables are marine technology, arboriculture, and perhaps international trade as opposed to trade internal to the peninsula.…”
Section: Discussion Of Principal Components Scores Trajectoriesmentioning
confidence: 90%